2015
DOI: 10.4103/0973-1482.147697
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, a biomarker of osteosarcoma

Abstract: Lowered serum Vitamin B 12 levels are possibly due to increased metabolic demand of the tumor. Raised hcy levels could be due to the contribution from rapidly proliferating cells. The present study suggests that these parameters can serve as useful markers for diagnosis and follow-up of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Although the mechanism for carcinogenesis is not well understood, associated low folate levels may lead to impaired DNA synthesis, repair, and methylation . In a study of 30 patients with osteosarcoma before treatment and 30 age‐ and sex‐matched controls, Kharb et al demonstrated higher homocysteine and folate levels but lower vitamin B12 levels in osteosarcoma patients than controls …”
Section: Resultsmentioning
confidence: 99%
“…Although the mechanism for carcinogenesis is not well understood, associated low folate levels may lead to impaired DNA synthesis, repair, and methylation . In a study of 30 patients with osteosarcoma before treatment and 30 age‐ and sex‐matched controls, Kharb et al demonstrated higher homocysteine and folate levels but lower vitamin B12 levels in osteosarcoma patients than controls …”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that low plasma vitamin B12 concentrations are associated with cancer [ 32 , 33 , 34 , 36 , 37 ]. Therefore, many patients could undergo extensive cancer treatments while having low vitamin B12 status.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review showed evidence of the association among vitamin B12 and/or folate, homocysteine (HCY) and osteoblastic and osteoclastic activity, and suggested the use of these biomarkers to assess bone metabolism (e.g., in osteosarcoma) (37)(38)(39)). An analysis published in 1964 (40) focused on the decrease in ALP serum levels following vitamin B12 supplementation therapy in patients with pernicious anemia, based on the case of a patient suffering from both pernicious anemia and PDB.…”
Section: Discussionmentioning
confidence: 99%